2014
DOI: 10.4132/koreanjpathol.2014.48.2.108
|View full text |Cite
|
Sign up to set email alerts
|

IMP3, a Promising Prognostic Marker in Clear Cell Renal Cell Carcinoma

Abstract: BackgroundInsulin-like growth factor II mRNA-binding protein 3 (IMP3) has been reported as a prognostic biomarker in various cancers. To validate IMP3 as a prognostic biomarker in renal cell carcinoma (RCC), we investigated the expression of IMP3, p53, and Ki-67, and their associations with clinicopathologic outcomes.MethodsWe studied 148 clear cell RCCs (CCRCCs) from patients who underwent radical nephrectomy. The expression levels of IMP3, p53, and Ki-67 were assessed by immunohistochemical staining and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…IMP3 expression has been associated with tumor formation, invasion, metastases, and cell proliferation (Ki-67-expression). Correlation between IMP3 expression and prognosis has also been established [34,35]. Similar correlations were found in our study with the melanoma xenograft mouse model that has not been previously published.…”
Section: Discussionsupporting
confidence: 90%
“…IMP3 expression has been associated with tumor formation, invasion, metastases, and cell proliferation (Ki-67-expression). Correlation between IMP3 expression and prognosis has also been established [34,35]. Similar correlations were found in our study with the melanoma xenograft mouse model that has not been previously published.…”
Section: Discussionsupporting
confidence: 90%
“…In pathological conditions, the expression of IMP3 is elevated in various malignant tumors (7). In addition, there were researches demonstrating that the possibility of distant carcinoma metastasis was associated with unfavorable prognosis (12)(13)(14)(15). DEK is a new member of DNA topology adjustment factors (10).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to VEGF-A, the results on the correlation between IMP3 expression and survival are also conflicting. Some studies identified IMP3 as an independent risk factor for poor prognosis in lung cancer and renal cell carcinoma patients (4244). However, in the present study, the difference in survival time between the IMP3-positive and negative groups was not statistically significant, as reported by another previous study (41).…”
Section: Discussionmentioning
confidence: 99%